Роль инклюзивного пропедевтического центра в предупреждении социального иждивенчества детей с ограниченными возможностями здоровья - Малярчук, Наталья Николаевна; Криницына, Галина Михайловна; Пащенко, Людмила Петровна (International Dialogues on Education Journal, 2017)
The article presents a way for solving the problem of social dependence among people with SEN. It illustrates the barriers in teaching children with special educational needs in different heterogeneous groups and risks for forming dependence in the process of inclusive education. The authors develop the idea of a propaedeutic education for children with SEN and discuss the importance of creating social and propaedeutic technologies for future school children to develop their social and moral competence. The article explicates the activity of the Propaedeutic Inclusive Center (PIC) and the social, human, methodological and organizational resources and principles of PIC.